2020
DOI: 10.1088/1674-1137/44/1/015101
|View full text |Cite
|
Sign up to set email alerts
|

Weak cosmic censorship conjecture in BTZ black holes with scalar fields *

Abstract: The weak cosmic censorship conjecture in the near-extremal BTZ black hole has been tested by the test particles and fields. It was claimed that this black hole could be overspun. In this paper, we review the thermodynamics and weak cosmic censorship conjecture in BTZ black holes by the scattering of the scalar field. The first law of thermodynamics in the non-extremal BTZ black hole is recovered. For the extremal and near-extremal black holes, due to the divergence of the variation of the entropy, we test the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 70 publications
(123 reference statements)
0
30
0
Order By: Relevance
“…Further exploration of Gwak indicates that both extremal and near-extremal Kerr-(anti) de Sitter black holes cannot be over-spun by classical fields [30]. Following this line, a series of works have shown that BTZ black holes [31,32], four-dimensional and higher-dimensional charged AdS black holes [33,34] cannot be over-spun or over-charged by classical test fields. These results suggest that the weak cosmic censorship conjecture is preserved in classical wave scattering process.…”
Section: Introductionmentioning
confidence: 95%
“…Further exploration of Gwak indicates that both extremal and near-extremal Kerr-(anti) de Sitter black holes cannot be over-spun by classical fields [30]. Following this line, a series of works have shown that BTZ black holes [31,32], four-dimensional and higher-dimensional charged AdS black holes [33,34] cannot be over-spun or over-charged by classical test fields. These results suggest that the weak cosmic censorship conjecture is preserved in classical wave scattering process.…”
Section: Introductionmentioning
confidence: 95%
“…However, this conjecture is violated in the near-extreme Reissner-Nordström black hole [12] and the near-extreme Kerr black hole [13]. The validity of weak cosmic censorship conjecture in the context of various black holes via the absorption of a charged or rotating particle has been discussed by many work [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32]. Although a lot of work has been done, no consistent conclusion has been reached.…”
Section: Introductionmentioning
confidence: 99%
“…Replacing the test particle with a test field, Semiz reviewed the validity of the WCCC in the dyonic Kerr-Newman black holes [11,12]. Other work about the validity of the WCCC are referred to [13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37]. Although a lot of work has been done, no consistent conclusion has been reached.…”
Section: Introductionmentioning
confidence: 99%